IDENTIFYING INTERIOR SPATIAL DIMENSIONS ACCORDING TO USER PREFERENCE: AN ASSOCIATIVE CONCEPT NETWORK ANALYSIS - Deny Willy Junaidy; Georgi V. Georgiev; Jake Kaner; Eljihadi Alfin (Jurnal Sosioteknologi, 2020)
This study proposed a fundamental technique for evaluating the preferences of interior space users by capturing their verbally expressed preferences and then determining word associations. To accomplish this, the Pajek visualization software for large network analysis was employed in conjunction with the USF Word Association dictionary to visualize the structures and network depths of the derived associative meanings. The generated associative words were then qualitatively categorized into taxonomic word groups to reveal 13 dimensions of perceived interior-environmental quality, as follows: House-related, Territorial, Impression, Activity, Active Element of Nature, Nature, Building Materials, Companion, Household Basics, Color, Location, Composition, and Time Period. A factor analysis was then conducted to sort the generated associative words according to Out- Degree Centrality/ODC score. These were validated into five factors that appeared to influence the comfort levels of interior space users. These five factors and 13 dimensions are useful as objective bases for determining the composition of adjectival pairs through the Semantic Differential (SD) method, which helps designers and architects evaluate interior space preferences.